(untitled) (Economics and region, 2018)
The paper analyzes the peculiarities of using the “Internet of Things” technologies in global production, namely in the field of international retail, global logistics and in the agro-industrial complex. The features of implementing this concept in the production process are outlined; it is determined that the main areas where the concept of the “Internet of Things” is being implemented are among the top 5 technological drivers of global competitiveness in the 21 st century. The study concluded that the concept of “Internet of Things” is multidisciplinary and presents not only advantages, but also risks, such as potential job loss and information security issues. Considering that the introduction of this concept will be a global trend in the coming years, it is necessary to form a systematic approach to the introduction of the “Internet of Things” technologies in our country, one which would be based on the adaptation of other states’ experience in this field